A Service Evaluation of More Than 27 000 Adults Referred to a Community Weight Management Program: 24-Month Outcomes - Josef Toon; Sarah-Elizabeth Bennett; Jacquie Lavin; Carolyn Pallister; Amanda Avery (SAGE Publishing, 2024)
Background: Obesity has a significant impact on healthcare resources with limited accessible support available through the NHS. This service evaluation determines 24-month efficacy of referral to an open-group behavioral program by BMI category and socioeconomic status. Methods: This retrospective, longitudinal study examined weight outcomes of adults living in England referred by healthcare professionals to Slimming World during 2016 who recorded at least 1 weight change. Primary outcome was % weight change at 3, 6, 12, and 24 months. Socioeconomic status was measured using the Index of Multiple Deprivation (IMD). Data from a post-referral questionnaire investigated self-reported changes in dietary and activity behaviors. Results: Twenty-seven thousand five hundred sixty (15.6% male) records were analyzed. Mean (SD) age and BMI on joining were 48.6 (14.80) years and 37.1 (6.31) kg/m 2 ; 91.7% had a BMI > 30 kg/m 2 . Mean (SD) % weight change was −5.6 (3.79), −7.1 (5.71), −7.5 (6.88), and −7.3 (6.88) at 3, 6, 12, and 24-months, respectively. At 24- months, differences in weight loss between BMI category were significant, ranging from 0.29% (35-<40 vs 40+) to 1.33% (25-<30 vs 40+). For IMD quintile only comparisons against Q1 and Q2 were significant, ranging between 0.36% (Q2 vs Q3) to 0.94% (Q1 vs Q5). Five thousand eight hundred sixty-two (21.2%) completed the post-referral questionnaire. There were no BMI category effects on dietary behaviors but changes in physical activity behaviors were lower within the higher categories albeit effect sizes were small (all ges < 0.001). IMD quintile influenced changes for sugary drinks, watching TV and avoiding moderate activity although effect sizes were small (all ges < 0.01). Conclusion: Following 12-week referral to a commercial weight management organization, a mean weight loss of over 7% was reported at 24-months. Adults with higher BMIs and a greater level of deprivation can benefit from the practical support offered as part of the referral, supporting weight loss and weight loss maintenance albeit with some inequality.